PEMANFAATAN TEPUNG UBI JAAR ORANGE (IPOMOEA TRIFIDA) SEBAGAI PENGGANTI SEBAGIAN JAGUNG TERHADAP PERSENTASE KARKAS, LEMAK ABDOMEN DAN ORGAN HATI AYAM KAMPUNG SUPER - Aturut, Jeni; Montong, Martina; Manangkot, Heidy; Lambey, Lucia (ZOOTEC, 2018)
UTILIZATION OF ORANGE SWEET POTATOES   FLOUR (Ipomoea trifida) AS A SUBSTITUTE OF CORN TO THE PERCENTAGE OF CARCASS, ABDOMINAL FATS AND LIVER ORGANS OF AYAM KAMPUNG SUPER. This study aims to determine the percentage of replacement of some corn with orange sweet potato flour (Ipomoea trifida) in ration   and its effect on carcass, abdominal fat and liver of super native chicken. This research used a 80 of chiken at six week old. Complete Randomized Design consist of 4 treatments and 5 replication were used as methods. The tratment were formulated as follow R0 Ration witout addition of orange sweet potatoes flour, R1 57% corn + 2.5 orange sweet potatoes flour, R2 55% corn + 5% orange sweet potatoes flour, R3 52.5 % corn + 7.5 % orange sweet potatoes flour. Research result showed that the addition of 2.5- 7.5% orange sweet potatoes flour in ration shows significant difference (P<0,05) on the percentage of carcass, where treatment using orange sweet potatoes flour up to 7.5% could increase the percentage of carcass. The treatment gave high sinificantly effect (P<0.01) on the percentage of abdominal fat. Percentage of liver on this research shows no sinificant effect (P>0.05). The conclution of this research is the giving of orange sweet potatoes can be used as substitution of corn untuil 7.5 % in ration because it can increase percentage of carcass, decrease of abdominal fat percentage and does not interfere.function of liver of  super native chicken.key words: orange sweet potatoes, a super native chicken